State dependence in labor market fluctuations: evidence, theory, and policy implications - Zanetti, F; Theodoridis, K (University of Oxford, 2018)
This paper documents state dependence in labor market ?uctuations. Using a Threshold Vector-Autoregression model, we establish that the unemployment rate, the job separation rate and the job ?nding rate exhibit a larger response to productivity shocks during periods with low aggregate productivity. A Diamond-Mortensen-Pissarides model with endogenous job separation and on-the-job search replicates these empirical regularities well. The transition rates into and out of employment embed state dependence through the interaction of reservation productivity levels and the distribution of match-speci?c idiosyncratic productivity. State dependence implies that the e?ect of labor market reforms is di?erent across phases of the business cycle. A permanent removal of layo? taxes is welfare enhancing in the long run, but it involves distinct short-run costs depending on the initial state of the economy. The welfare gain of a tax removal implemented in a low-productivity state is 4.9 percent larger than the same reform enacted in a state with high aggregate productivity.